2020
DOI: 10.1182/bloodadvances.2020001657
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag for patients with moderate aplastic anemia or uni-lineage cytopenias

Abstract: There is no standard or widely effective treatment of patients with moderate aplastic anemia (MAA) or hypo-productive uni-lineage cytopenias (UC). Eltrombopag (EPAG), a small molecule thrombopoietin mimetic, has previously been shown to result in durable multi-lineage hematologic responses with low toxicity in patients with refractory severe aplastic anemia (SAA). Its safety and efficacy in MAA are unknown. This prospective phase 2 study enrolled previously untreated and treated MAA and UC patients with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 30 publications
2
35
1
1
Order By: Relevance
“…Consequently, the NIH performed a dose-escalating study in MAA and unilineage cytopenic syndromes. 25 Eltrombopag was given at doses from 50 mg up to 300 mg and hematologic response was assessed after 14–20 weeks. Half of the study population responded in at least one previously affected lineage and the treatment could be stopped in the majority of the responding patients.…”
Section: The Clinical Evidence Of Eltrombopag In Saamentioning
confidence: 99%
“…Consequently, the NIH performed a dose-escalating study in MAA and unilineage cytopenic syndromes. 25 Eltrombopag was given at doses from 50 mg up to 300 mg and hematologic response was assessed after 14–20 weeks. Half of the study population responded in at least one previously affected lineage and the treatment could be stopped in the majority of the responding patients.…”
Section: The Clinical Evidence Of Eltrombopag In Saamentioning
confidence: 99%
“…However, in the age-matched subgroup, in which patients were younger, there was less relapse as well as clonal evolution implying an age-related effect. Although no evidence for the increase of clone evolution rate has been identified when EPAG+IST was compared with the history controls of IST alone as the frontline therapy so far (23,29), we do see the relapse when EPAG or IST was tapered or withdrawn (36,42). VSAA patients usually exhibit higher chances of relapse and clonal evolution when compared with SAA patients (43).…”
Section: Discussioncontrasting
confidence: 54%
“…Aged patients usually exhibit poor response to treatment when compared with the younger ones, for either IST or HSCT (35)(36)(37). Under this circumstance, we found that EPAG+IST had a very similar ORR (lower in absolute number) than the haplo-HSCT (81% in the EPAG+IST group and 86% in the haplo-HSCT group, p = 0.23).…”
Section: Discussionmentioning
confidence: 63%
“…We present evidence that addition of EPAG during DBA iPSC differentiation rescues at least in part the block in erythroid maturation recapitulated in this model. These findings and the recent report of a robust erythroid response to EPAG in a steroid-refractory DBA patient with a de novo mutation in RPS19 [42] suggest that EPAG may represent an alternative therapeutic modality for subjects with DBA. A single-arm phase I/II pilot trial (NCT04269889) has recently received approval at our institution to further assess safety and efficacy of EPAG in DBA patients.…”
Section: Discussionmentioning
confidence: 59%